2006
DOI: 10.1508/cytologia.71.101
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Clastogenic Effects of the Extract from Medicinal Plant Rosmarinus officinalis L. on Wistar Rat Bone Marrow Cells

Abstract: SummaryThe use of medicinal plants by the general population is an old and still widespread practice, which makes studies of their mutagenicity essential. Rosmarinus officinalis, long used in folk medicine, is used as an antispasmodic in renal colic and dysmenorrhoea, in relieving respiratory disorders, to stimulate growth of hair and has choleretic, hepatoprotective and antitumerogenic activity. The aim of this study was to evaluate the clastogenic potential of the Rosmarinus officinalis hidro-alcoholic extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…As it was expected, the group who received the dose of CP (positive control) increased the frequency of MN in normochromic and polychromatic erythrocytes and decreased the proportion of PCE (Table 2), thus demonstrating the validity of the experimental design. Our findings are in accordance with the study of Gaiani et al, 22 who found that R. officinalis hydroalcoholic extract at doses of 6.43, 100 and 200mg/kg body weight, did not induce statistically significant increases on MN frequency and MNPC frequency was increased but without significance. This differs from our results, since the three doses used in our study decreased MNPCE frequency, this could be explained, since it has been reported that RTE contains many substances like phenols with antioxidant and anti-lipoperoxidant activity Erkan et al, 1 Wang et al 23 The literature mentions that the combination of two acid-phenols, leads to an increase in antioxidant efficacy activity.…”
Section: Discussionsupporting
confidence: 93%
“…As it was expected, the group who received the dose of CP (positive control) increased the frequency of MN in normochromic and polychromatic erythrocytes and decreased the proportion of PCE (Table 2), thus demonstrating the validity of the experimental design. Our findings are in accordance with the study of Gaiani et al, 22 who found that R. officinalis hydroalcoholic extract at doses of 6.43, 100 and 200mg/kg body weight, did not induce statistically significant increases on MN frequency and MNPC frequency was increased but without significance. This differs from our results, since the three doses used in our study decreased MNPCE frequency, this could be explained, since it has been reported that RTE contains many substances like phenols with antioxidant and anti-lipoperoxidant activity Erkan et al, 1 Wang et al 23 The literature mentions that the combination of two acid-phenols, leads to an increase in antioxidant efficacy activity.…”
Section: Discussionsupporting
confidence: 93%
“…41 A hydroalcoholic extract of rosemary was not genotoxic in a chromosomal aberration assay or a micronucleus test in rats. 53 A mixture containing 19% R officinalis (rosemary) leaves, 71.5% St John's wort, and 9.5% spirulina induced in mice statistically significant increases in MNPCEs at 760 and 1,520 mg/kg bw/d in a micronucleus test; in frequency of aneuploidy, percent polyploidy, and total percent aberrations with 760 and 1,520 mg/kg bw/d in a chromosomal aberration assay; and in frequency of banana-shaped, swollen acrosome, and triangular head sperm abnormalities and percent total spermatozoa abnormalities at 1,520 mg/kg bw/d in a spermatozoa abnormality assay. 54 Rosmarinus officinalis (rosemary) leaf extract was shown to have antimutagenic potential, in vitro, in an Ames test with Salmonella typhimurium and in Comet assays in a human hepatoma cell line.…”
Section: Genotoxicitymentioning
confidence: 99%
“…Although rosemary oil increased DNA damage in liver and leukocyte cells, and chromosome aberrations, at the 2000 mg/kg dose, the results of polychromatic to normochromatic erythrocyte ratio and mitotic index assay showed that a single dose of rosemary oil did not negatively affect hematopoiesis. Gaiani et al (2006) investigated the genotoxic potential of hydro-alcoholic extract of R. officinalis in vivo in bone marrow cells of Wistar rats by micronucleus and chromosome aberration assays and concluded that at 6.43, 100 and 200 mg/kg body weight doses, this extract is not mutagenic. We used higher doses of rosemary oil, the smallest dose tested (300 mg/kg) was chosen on the basis of ED 50 of 261 mg/kg, obtained by Faria (2005) in an anti-inflammatory and analgesic investigation.…”
Section: Discussionmentioning
confidence: 99%